The effectiveness of promotional tools implemented by Institute of Management Melaka (IMM) / Mohd Fadzil Mohd Daud - Mohd Daud, Mohd Fadzil (Faculty of Business and Management, 2006)
This research is carried out to investigate the assessment of the promotional tools that have been implemented by Institute of Management Melaka (IMM). IMM is a subsidiary of Melaka State Government and is managed by the Melaka Chief Minister Department. The main functions of IMM are to provide important information, to plant and implement training programs, services of human resource development and organizers for seminars, luncheon talks and dinner talks on behalf of the Melaka Chief Minister's Department. Various promotional activities have been implemented by IMM, but people still does not know the existence of IMM. This study will try to assess the effectiveness on these area of promotional tools and also to identify which of the promotional implemented by IMM is mostly effective. It is hoped that IMM will choose only an effective promotional tool and not one that is not effective. Suggestions and recommendations also will be included in this research. Literature review from the previous authors and researchers is also included in this study. It could be used as a source of reference for the benefit of this research. The authors included are Kotler & Armstrong and also N.K. Malhotra.